Anforderungen und Randbedingungen für den Einsatz optischer Messsysteme zur In-Line-Prüfung additiv gefertigter Bauteile - Hartmann, Wito; Hausotte, Tino; Drummer, Dietmar; Wudy, Katrin (RTejournal - Forum für Rapid Technologie, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.lfmt.anford

Automated extraction and assessment of functional features of areal measured microstructures using a segmentation-based evaluation method - Hartmann, Wito; Loderer, Andreas (Surface Topography: Metrology and Properties, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.lfmt.automa

Calibration Concept for Dimensional Measurements with Optical Multiscale Multi-Sensor Systems - Loderer, Andreas; Hartmann, Wito; Hausotte, Tino (AMA Conferences 2015 - SENSOR 2015 and IRS² 2015, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.lfmt.calibr

Discarding prospective students from engineering - experiences with an aptitude assessment procedure - Weckenmann, Albert; Kreis, Oliver; Hartmann, Wito; Werner, Teresa (Proceedings of 37th Annual Conference of SEFI. "Attracting young people to engineering. Engineering is fun!", 2009)
Since many years, an extremely high rate of dropouts is to be noticed on engineering study courses. In order to decrease the number of failing students, an aptitude assessment procedure has been established for the bachelor study course of Mechanical Engineering at the University of Erlangen-Nuremberg. The prospective students are assessed regarding the final school grades as well as their personal aptitude for a technical profession. First experiences with the execution and impact of the procedure are discussed in order to be able to improve the executed measure. Thus, on long term, a higher output of qualified engineers shall be achieve
UnivIS-Import:2015-04-16:Pub.2009.tech.FT.FT-QMFMT.discar

Function-oriented Measurements - the Path from Macro to Micro and Nano Range - Weckenmann, Albert; Hartmann, Wito (Proceedings of the 5th Manufacturing Engineering Society International Conference, 2013)

Funktionsorientierte Bewertung bei der Druckwalzenherstellung - Tillmann, Andreas; Weckenmann, Albert; Hartmann, Wito; Schmidt, Heiko; Schulze, Volker; Stockey, Stefan; Chlipala, Mattäus (2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-QMFMT.funkti_0

Funktionsorientierte Bewertung bei der Herstellung von Einspritzdüsen - Lenk, Andreas; Hopp, Benjamin; Wiedenhöfer, Thomas; Weckenmann, Albert; Hartmann, Wito; Schmidt, Heiko (2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-QMFMT.funkti_2

Funktionsorientierte Bewertung und deren Nutzung für die Kurbelwellenfertigung - Zimmermann, Wolfram; Holdik, Karl; Happek, Benedikt; Schreiber, Leo; Weber, Michael; Hartmann, Wito; Schulze, Volker; Chlipala, Mattäus; Stockey, Stefan; Pabst, Rüdiger; Weckenmann, Albert; Schmidt, Heiko (2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-QMFMT.funkti_9

General Approach and Procedures on the Assessment of Wear to Cutting Tools - Hartmann, Wito; Hausotte, Tino (Measurement Good Practice Guides, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.lfmt.genera

Holistic measurement in the sheet-bulk metal forming process with fringe projection - Ohrt, Christoph; Hartmann, Wito; Weickmann, Johannes; Kästner, Markus; Weckenmann, Albert; Hausotte, Tino; Reithmeier, Eduard (Key Engineering Materials KEM, 2012)
Sheet-bulk metal forming (SBMF) is a new forming technology, currently developed by several companies and research institutes. SBMF is uniting the advantages of sheet and bulk metal forming processes in terms of flexibility and possibilities. Thus the limitations of each forming process can be exceeded and the workpiece complexity can be increased. It also creates high demands on the inspection and verification of parts and tools, especially in the field of in-situ wear detection of the forming tool and its impacts on the workpiece. Two optical testing methods for fulfilling these inspection tasks are introduced and presented: On the one hand the endoscopic fringe projection as a flexible small scale optical measurement principle with high depth of focus and accuracy for the acquisition of filigree form elements for a continuous abrasion determination and on the other hand the multi-scaled fringe projection for a holistic cycle time compatible measurement of the workpiece for an adapted, multiscale deviation analysis. The development and advantages of both systems for the sheet bulk metal forming process are shown.© (2012) Trans Tech Publications.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-QMFMT.holist_1
Keywords: Endoscopy; Fringe projection; Multi scale; Sensor layout; Sheet-bulk metal forming

Incremental In-line Measurement Technique for Additive Manufacturing - Hartmann, Wito; Hausotte, Tino; Kühnlein, Florian; Drummer, Dietmar (Proceedings, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.lfmt.increm

Measurement Procedures and Evaluations Methods for the Extraction and Assessment of Functional Features of Microstructured Surfaces - Hartmann, Wito; Loderer, Andreas (Abstracts of the ISMQC 2013, 2013)
The paper describes an approach how to measure func-tion-oriented with appropriate measurement technology and evaluation methods. At first important features of the surface, which have a large influence on the functional behaviour, are determined based on a physical-mathematical model of the function. Then - adapted to the measuring task - it is de-scribed how to measure these features starting with the selec-tion of suitable measurement procedures (optical/tactile, 2D/3D, multi-scale data fusion). Moreover, the evaluation of the measurement values is also crucial. Automated evaluation procedures based on segmentation techniques and autocorre-lation methods were presented using examples of microstruc-tures for the improvement of sliding and ink transfer for print-ing machines. These procedures allow extracting important functional properties of the measured 3D surface and their quantitative evaluation.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.lfmt.measur_8
Keywords: Function-oriented; Microstructure; Model-based test technique; Segmentation techniques; Surface metrology

Measurement strategy for a production-related multi-scale inspection of formed work pieces - Loderer, Andreas; Galovskyi, Bogdan; Hartmann, Wito; Hausotte, Tino (Proceedings of the 11th Global Conference on Sustainable Manufacturing - Innovative Solutions, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.lfmt.measur_1

Optische In-Line-Prüftechnik zur Qualitätssicherung beim selektiven Strahlschmelzen von Kunststoffen - Galovskyi, Bogdan; Hausotte, Tino; Loderer, Andreas; Hartmann, Wito (3. Industriekolloquium des Sonderforschungsbereichs 814 - Additive Fertigung, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.lfmt.optisc

Optische Messsysteme zur In-Line-Prüfung im additiven Fertigungsprozess - Hausotte, Tino; Hartmann, Wito; Timmermann, Martin; Galovskyi, Bogdan (Industriekolloquium des Sonderforschungsbereichs 814 - Additive Fertigung, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.lfmt.optisc

Qualifying measuring systems by using Six Sigma - Loderer, Andreas; Galovskyi, Bogdan; Hartmann, Wito; Hausotte, Tino (Abstracts of the ISMQC 2013, 2013)
The technology of sheet-bulk metal forming enables the production of complex workpieces with filigree surface structures in only a few forming steps. In order to provide a rapid and production-related workpiece inspection of not only large workpiece features, but also small features in an appropriate quality, a multi-sensor optical measurement system with different resolutions is required. Workpiece features of medium size can be measured by two types of fringe projection sensors. With a structured approach according to Six Sigma, which is based on the five phases design, measure, analyze, improve and control complex tasks are divided into smaller individual problems. In each phase the Six Sigma method recommends tools for solving the individual problems effectively. With the support of the Six Sigma guideline an exemplary sheet-bulk metal forming workpiece feature is used in order to qualify the two measuring systems for a production-related measurement. After defining the explicit goal for the investigations, a detailed analysis of the measurement process leads to a couple of relevant influences. These are input factors for the design of experiments. By a full factorial design, not only an influence of a factor itself, also the interactions between multiple factors can be detected. In the analyze-phase, these results are calculated by different statistical methods. To present the results in a comprehensible way several types of diagrams are used. The shown approach gives an example for a traceable and methodical way to qualify a measurement system for challenging measurement tasks.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.lfmt.qualif
Keywords: Evaluation of sensor performance; Fringe projection; Sheet-bulk metal forming; Six Sigma

Qualifying measuring systems by using Six Sigma - Loderer, Andreas; Galovskyi, Bogdan; Hartmann, Wito; Hausotte, Tino (Key Engineering Materials, 2014)
The technology of sheet-bulk metal forming enables the production of complex workpieces with filigree surface structures in only a few forming steps. In order to provide a rapid and production-related workpiece inspection of not only large workpiece features, but also small features in an appropriate quality, a multi-sensor optical measurement system with different resolutions is required. Workpiece features of medium size can be measured by two types of fringe projection sensors. With a structured approach according to Six Sigma, which is based on the five phases design, measure, analyze, improve and control complex tasks are divided into smaller individual problems. In each phase the Six Sigma method recommends tools for solving the individual problems effectively. With the support of the Six Sigma guideline an exemplary sheet-bulk metal forming workpiece feature is used in order to qualify the two measuring systems for a production-related measurement. After defining the explicit goal for the investigations, a detailed analysis of the measurement process leads to a couple of relevant influences. These are input factors for the design of experiments. By a full factorial design, not only an influence of a factor itself, also the interactions between multiple factors can be detected. In the analyze-phase, these results are calculated by different statistical methods. To present the results in a comprehensible way several types of diagrams are used. The shown approach gives an example for a traceable and methodical way to qualify a measurement system for challenging measurement tasks.
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.lfmt.qualif
Keywords: Evaluation of sensor performance; Fringe projection; Sheet-bulk metal forming; Six Sigma